Hybrid Learning in Islamic Religious Education for Generation Z: An Integrative Literature Review - Basuki; Ahd. Mujahid (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study examines how hybrid learning can be conceptually designed for Islamic Religious Education to address the diverse characteristics of Generation Z while preserving moral, spiritual, and character-forming objectives. An integrative literature review was conducted using publications retrieved from Scopus, Web of Science, Education Resources Information Center, Dimensions, and supplementary Google Scholar searches covering 2004–2026. Eligible empirical, theoretical, and review studies were appraised and analyzed through qualitative content analysis and thematic synthesis. The review identified five interdependent domains: enabling conditions, instructional-design principles, learning processes, mediating roles, and multidimensional outcomes. The findings show that purposeful integration of face-to-face, synchronous, and asynchronous activities is more consequential than the quantity or sophistication of technology. Flexibility supports learning only when accompanied by instructional structure, teacher guidance, student self-regulation, equitable access, and institutional support. Cognitive learning does not automatically generate moral or spiritual development; value internalization requires reflection, modelling, authentic application, and sustained interaction. The study challenges technologically deterministic and homogeneous “digital native” assumptions about Generation Z and introduces spiritual-reflective presence as an extension of teaching, social, and cognitive presence in hybrid-learning environments. The resulting evidence-informed framework connects technological affordances with Islamic pedagogy, teacher mediation, learner readiness, and cognitive, affective, social, moral, and spiritual outcomes. It provides theoretically testable propositions and a foundation for expert validation, design-based implementation, mixed-method evaluation, and longitudinal research across different Islamic educational settings. It also offers practical guidance for teacher development and inclusive institutional planning.